Kebijakan Kriminal dalam Penanganan Tindak Pidana Terorisme di Indonesia - Rozaq, Mubdiul; Fahmiron, Fahmiron (UNES Law Review, 2023)
Law Number 5 of 2018 has regulated the Eradication of Indonesian Terrorism Crimes. However, the number of acts of terrorism in Indonesia has not decreased even though the laws and regulations in Indonesia have provided strict sanctions against the perpetrators of terrorism. Crime prevention policies or efforts are urgently needed to reduce the number of acts of terrorism in Indonesia. The problems examined in this thesis are First, how is the criminal policy in handling criminal acts of terrorism in Indonesia? Second, how can the handling of criminal acts of terrorism be better in the future in Indonesia? This research is a legal research with descriptive analytical specifications. The approach used is a normative juridical approach. The data used are secondary data and primary data collected through library research. The data obtained were analyzed qualitatively and presented in an analytical descriptive form. The results of this study are first, criminal policy in handling criminal acts of terrorism in Indonesia is the formation or renewal of legal substance with the issuance of RI Law Number 5 of 2018 concerning Amendments to RI Law Number 15 of 2003 concerning Eradication of Criminal Acts of Terrorism. Second, better handling of Terrorism Crimes in the Future is to change Article 14 by adding 1 (one) new paragraph, namely paragraph (2) concerning mitigating crimes against perpetrators if the crime referred to in paragraph (1) does not occur. Furthermore, amending Article 17 paragraph (2) regarding criminal liability for corporations that commit acts of terrorism.